Religious markers reduce perceived trustworthiness in a Muslim-majority country - Joshua Hellyer; Johanna Gereke; Ozan Aksoy; Emily Hellriegel; Reinhard Schunck (Proceedings of the National Academy of Sciences, 2026)
First impressions often hinge on visible cues, leading people to infer the trustworthiness of strangers from their appearance and dress. While religiosity is generally associated with greater perceived trustworthiness, little is known about how visible religious markers, such as clothing and grooming styles, shape trust judgments in Muslim-majority societies, where such signals are widespread and easily recognizable. We examine this question using a large-scale vignette experiment embedded in a nationally representative face-to-face survey in Turkey. By experimentally varying profile characteristics, we identify the causal effect of a Muslim headscarf or beard on perceived trustworthiness. Contrary to expectations, individuals displaying these religious badges are generally viewed as less trustworthy than otherwise identical profiles, even by highly religious respondents. Mediation analyses show that these effects arise because religious badges signal multiple attributes, not only religiosity but also political orientation and physical attractiveness—and that these inferred meanings differ by gender: women’s headscarves and men’s beards prompt distinct patterns of inference. These findings show that visible religious markers shape trust judgments through multivalent social inferences rather than perceived piety alone. The results highlight how observers draw on broader social and political associations when interpreting religious markers, providing evidence on how public expressions of religion affect everyday trust judgments.